THE FIRST 24 HOURS. - SHELHART, MARK (Public Management (00333611), 2015)
The article offers suggestions for officials to deal with suspected data breach within 24 hours of the incident. Topics discussed include maintaining time records by writing down the details of the occurrence and people involved in the matter, analyzing the situation by reacting quickly and implementing a response plan in an organized manner and leaving the power on find a trail in computer memory by hackers.